Flocculation inSaccharomyces cerevisiae is regulated by RNA/DNA helicase Sen1p. Issue 20 (10th September 2015) - Singh, Vikash; Azad, Gajendra Kumar; Sariki, Santhosh Kumar; Tomar, Raghuvir S.
Abstract : The Nrd1–Nab3–Sen1 (NNS) complex terminates transcription of non‐coding RNA genes and mediates degradation of the produced transcript by the nuclear exosome. The NNS complex also represses some stress response genes, by stimulating premature termination. A well‐characterized stress response in yeast is flocculation, where cells aggregate to form flocs under expression of lectin‐encoding genes designated as FLOs. In this study, we demonstrated the role of the NNS complex and Rrp6p in the expression of flocculation genes: FLO1, FLO5, FLO9, and FLO10 . Furthermore, a deletion mutant of the RNA processing machinery ( RNT1 ), and SEN1 mutants that are unable to interact with Rnt1p, exhibit a flocculation phenotype. In summary, we have identified a cooperative role of Rnt1p, Rrp6p and the NNS complex in the repression of FLO genes. Abstract : Sen1p mutants that are unable to interact with Rnt1p induce upregulation of FLO genes. Rnt1p deletion stimulates flocculation. NNS complex mutants induce upregulation of FLO genes and flocculation.